Suspended silicon waveguides for long-wave infrared wavelengths - Sánchez-Postigo, A. (2019)
In this Letter, we report suspended silicon waveguides operating at a wavelength of 7.67 μm with a propagation loss of 3.1±0.3  dB/cm. To our knowledge, this is the first demonstration of low-loss silicon waveguides at such a long wavelength, with loss comparable to other platforms that use more exotic materials. The suspended Si waveguide core is supported by a sub-wavelength grating that provides lateral optical confinement while also allowing access to the buried oxide layer so that it can be wet etched using hydrofluoric acid. We also demonstrate low-loss waveguide bends and s-bends.